Komunitas Fitoplankton sebagai Bioindikator Kualitas Air Sungai Kali Surabaya - Salsabila Putri, Desi; Hendriyanto Cahyonugroho, Okik (Spizaetus: Jurnal Biologi dan Pendidikan Biologi, 2025)
The Kali Surabaya River is one of Indonesia's rivers impacted by pollution from industrial and domestic activities. Conventional water pollution analysis generally relies on physicochemical parameters and often overlooks biological factors. This study aims to analyze phytoplankton biological indices as bioindicators of water quality and integrate them with the results of the Pollution Index (PI). Water samples were collected using purposive sampling from four stations for the analysis of physicochemical parameters and phytoplankton identification using a 40 µm plankton net. The obtained data were analyzed by calculating the phytoplankton diversity index and the Pollution Index (PI). During the two-week research period, the phytoplankton community structure was dominated by Scenedesmus sp. (22.92%), Nitzschia sp. (12.76%), and Merismopedia sp. (10.75%), indicating organic pollution and eutrophication in the Kali Surabaya River. The PI results classified the river as slightly polluted (1.8 – 4.935). This study concludes that the integration of phytoplankton bioindicators with the pollution index analysis is effective in indicating pollution status and condition.